PERAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM UPAYA PEMBENTUKAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB SISWA SMA NEGERI 1 CIOMAS - Muhammad Iqbal Fipli (Universitas Pahlawan Tuanku Tambusai, 2022)
This research has a background that there are still many attitudes that reflect the lack of discipline and responsibility in students at SMA Negeri 1 Ciomas such as being late for class, neglecting to do assignments, neglecting to be responsible at school, and other violations. . In this case, the role of PAI teachers is very important in educating morals and shaping the character of discipline and responsibility in students, as a provision to become the nation's successors in the future. In addition, teachers at SMA Negeri 1 Ciomas, especially PAI teachers also play an important role in being role models for students to form and instill the character of discipline and responsibility in each of them. This study uses a qualitative approach, aiming to answer questions from the formulation of the problem in this research and to study intensively about how the environment, position, and field conditions of a research unit interact. The research method, which is based on postpositivism or interpretive philosophy, is used to examine the condition of natural objects, where the researcher is the key instrument, the data collection technique is done by triangulation (a combination of observation, interviews, and documentation), the data obtained tend to be qualitative data, data analysis is qualitative, and qualitative research results can be in the form of finding potential and problems, uniqueness of objects, meaning of an event, processes and social interactions, certainty of data truth, construction of phenomena, findings of hypotheses. The findings of this study indicate that in shaping the character of students' discipline and responsibility, PAI teachers play an active role as educators, tutors, role models, advisors/motivators, and as evaluators. In addition, the teacher also plays an active role in being a supervisor and evaluator for students in forming the character of students' discipline and responsibility, and always providing good examples in efforts to build these characters. The factors that influence the formation of the character of discipline and responsibility of SMA Negeri 1 Ciomas students are teachers, parents, peers, and the environment where students live, where these factors can be supporting factors or inhibiting factors depending on the form of influence given to the students of SMA Negeri 1 Ciomas. Keywords: Islamic Education Teacher, Character, Discipline, Responsibility.